Sistem Informasi Monitoring Integrasi Program pada Direktorat PMPUPO Badan POM - Alfin Fauza; Safaruddin Hidayat Al Ikhsan; Berlina Wulandari (Teknik Informatika Universitas Pamulang, 2022)
The Directorate of Community Empowerment and Processed Food Business Actors (PMPUPO), is one of the Directorates within the Deputy for Processed Food Supervision of the Food and Drug Monitoring Agency (BPOM), has the task of implementing policies, drafting norms, standards, procedures, criteria, implementing technical guidance and supervision, as well as evaluation and reporting. The PMPUPO 2020 website has a lot of data, so the program monitoring process is less effective. That way the program data processing process is difficult to access by the leadership so that sometimes it results in discrepancies between the reports made and the existing data. Therefore, in this study, an information system for monitoring program integration at the PMPUPO Directorate was created to make it easier for leaders to access or obtain strategic data. The data used in this study were obtained from the Directorate of PMPUPO. The research method used includes three main parts, namely data collection, system analysis and development of a linear sequential model system. Based on the results of system testing that has been carried out, this system has functioned well, which is indicated by the availability of the speed of information obtained in the form of distribution maps, graphs, and reports so that it can make it easier for leaders to access or obtain information.